2017
DOI: 10.37134/mrj.vol6.8.2017
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Peranan Pemimpin Pembelajaran Profesional dan Model Pembelajaran Profesional dengan Amalan Guru Sekolah Menengah Harian di Malaysia

Abstract: Tujuan utama kajian ini ialah untuk mencadangkan satu model persamaan struktural bagi mengenal pasti hubungan antara peranan pemimpin pembelajaran profesional dan model pembelajaran profesional dengan amalan guru. Selain itu, kesan langsung dan kesan tidak langsung dalam kalangan pemboleh ubah-pemboleh ubah juga turut ditunjukkan.Kajian empirikal ini telah dijalankan di empat puluh satu buah sekolah menengah harian di Malaysia. Data diperoleh menerusi soal selidik terhadap 372 orang guru yang dipilih melalui p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
2
6
0
1
Order By: Relevance
“…Furthermore, the study by Jose and Musa [39] found that the distributive leadership of school administrators has a significant influence on work commitment among teachers. School administrators must practice the distributive leadership dimensions to increase teacher commitment to the maximum level [31]. This statement is in line with the intention of MEDP 2013-2025, which introduced distributive leadership in the 2nd wave (2016-2020) for school administrators to become mentors, facilitators, developers, and examples of best practices in schools to be emulated by teachers [1].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Furthermore, the study by Jose and Musa [39] found that the distributive leadership of school administrators has a significant influence on work commitment among teachers. School administrators must practice the distributive leadership dimensions to increase teacher commitment to the maximum level [31]. This statement is in line with the intention of MEDP 2013-2025, which introduced distributive leadership in the 2nd wave (2016-2020) for school administrators to become mentors, facilitators, developers, and examples of best practices in schools to be emulated by teachers [1].…”
Section: Discussionmentioning
confidence: 79%
“…Through this study, the researchers used the theory of professional learning practice highlighted by previous studies [29]- [31]. Here are the basic practices that have been highlighted by the three founders of the professional learning theory.…”
Section: Professional Learning Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Teachers' learning should not stop once they have completed their education at university but should continue until they have completed programmes to improve their selfprofessionalism after they have worked in the classroom. Continuous learning while on the job seeks to develop and empower teachers with the requisite knowledge and skills to keep up with changes in existing education policies and frameworks that strive to transform education to be better and more quality in line with global requirements (Ministry of Education, 2013;Mansor, Norwani & Yunus, 2014).…”
Section: Issues Of Teacher Professionalism In Malaysiamentioning
confidence: 99%